2012
DOI: 10.1134/s1021443712040115
|View full text |Cite
|
Sign up to set email alerts
|

Starch-related enzymes during potato tuber dormancy and sprouting

Abstract: Activities of enzymes presumably involved in starch biosynthesis (ADP glucose pyrophosphory lase, AGPase) and/or breakdown (starch phosphorylase, STP; amylases) were determined during potato (Solanum tuberosum L.) tuber dormancy and sprouting. Overall activities of all these enzymes decreased dur ing the first stage of tuber dormancy. No clear changes were detected at the time of dormancy breaking and sprouting. However, when AGPase activity was monitored by in situ staining during the entire dormancy period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…These findings supported the traditional opinion that the bud is a site of the nutrient accumulation and storage and that plants with more buds show more nutrient accumulation [60]. A previous study also indicated that tubers are storage organs that accumulate starch during the development of potato [61]. Starch degradation results in an increase in the soluble sugar concentration; thus, starch may play an important role in the accumulation of endogenous soluble sugars in cells [62].…”
Section: The Role Of Sugars In Axillary Bud Developmentsupporting
confidence: 83%
“…These findings supported the traditional opinion that the bud is a site of the nutrient accumulation and storage and that plants with more buds show more nutrient accumulation [60]. A previous study also indicated that tubers are storage organs that accumulate starch during the development of potato [61]. Starch degradation results in an increase in the soluble sugar concentration; thus, starch may play an important role in the accumulation of endogenous soluble sugars in cells [62].…”
Section: The Role Of Sugars In Axillary Bud Developmentsupporting
confidence: 83%
“…For the activity determination of starch-metabolizing enzymes, the crude enzyme was extracted according to Nakamura et al ( 1989 ) and Sergeeva et al ( 2012 ). All the procedures were carried out at 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…This is related to the adequacy of energy reserves in the form of carbohydrates in the tubers which are used by the enzymes during the germination process. During the tuber development process, the presence of amylase activity is important in the starch cycle, where Β-amylase activity decreases at the beginning of dormancy and then increases after initiation of sprouts (Sergeeva et al, 2012).…”
Section: Length Of Sproutsmentioning
confidence: 99%